Improved Radioenzymatic Assay for Spectinomycin - Cannon, Janne G. (1978)
The sensitivity and reproducibility of the radioenzymatic adenylylating assay for spectinomycin were improved by modifications of the assay procedure and by partial purification of the enzyme. The presence of Bacillus subtilis ribosomes or S-150 fraction in the enzymatic reaction mixture interfered with the ability to measure spectinomycin by this method.